Pengaruh Terapi Bermain Plastisin Terhadap Tingkat Kecemasan Akibat Hospitalisasi Pada Anak Usia 3-6 Tahun Di RSUD Dr.RM Djoelham Binjai - Damanik, Rani; Sri Dearmaita Purba; Frida Liharris Saragih; Tasya A.P.Dalimunthe (JURNAL TEKNOLOGI KESEHATAN DAN ILMU SOSIAL (TEKESNOS), 2024)
Play therapy is a good activity to deal with anxiety due to hospitalization so as to speed up the child's healing process. This study aims to determine the effect of playing plasticine on the level of anxiety due to hospitalization in children aged 3-6 years at RSUD DR RM Djoelham Binjai. This type of research is a quantitative research with a Quasi-Experimental method and uses a pretestposttest design with a control group. The sample in this study was 30 people, collecting data using a direct questionnaire. Sampling used the slovin formula technique, the normality test used the Shapiro-Wilk and data analysis used the paired t-test. The results of the normality test before being given education were 0.938 and Sig. .082 after education 0.897 and Sig. 0.007 which is normally distributed. The results of the study were obtained before being given plasticine play therapy, the level of severe anxiety was 15 children (50.0%). And after being given plasticine play therapy in children, the level of severe anxiety decreased to 6 children (20.0%). The results of the paired ttest obtained a significance value obtained from the calculation results, namely p value 0.023.